THE INFLUECE OF ACCOUNTABILITY, AUDIT KNOWLEDGE, AND AUDITOR PROFESSIONALISM ON AUDIT QUALITY AT BPKP EAST JAVA - Laeli Romandhoni; Nur Lailiyatul Inayah; Ria Dini Apriliasari; Muhammad Habibie Al Hamzah (LPPM STIE YKPN Yogyakarta, 2025)
Auditors play a crucial role in the management and supervision of the financial sector by providing accurate and reliable information to support the policy setting stage. This study intends to identify and analyze the simultaneous influence of accountability, audit knowledge, and auditor professionalism on the quality of audits conducted by BPKP in East Java. The method used in this research is a quantitative approach, where data is collected through the distribution of questionnaires. The target population in this study consisted of 143 internal auditors at BPKP East Java, with a sample of 105 people taken. The sampling technique applied is probability sampling with stratified random sampling method. for data testing, validity and reliability tests were carried out. In data analysis, multiple linear regression analysis methods and hypothesis tests, namely the F test and t test, were used. The results obtained from this study indicate that accountability, audit knowledge, and auditor professionalism have a simultaneous impact on the quality of audits carried out by BPKP East Java. Among these variables, auditor professionalism distributes the most significant influence on audit quality at BPKP East Java.